Homeostatic control of brain function – new approaches to understand epileptogenesis - Boison, Detlev; Sandau, Ursula S.; Ruskin, David N.; Kawamura, Masahito; Masino, Susan A. (Frontiers in Cellular Neuroscience, 2013)
Neuronal excitability of the brain and ongoing homeostasis depends not only on intrinsic neuronal properties but also on external environmental factors; together these determine the functionality of neuronal networks. Homeostatic factors become critically important during epileptogenesis, a process which involves complex disruption of self-regulatory mechanisms. Here we focus on the bioenergetic homeostatic network regulator adenosine, a purine nucleoside whose availability is regulated largely by astrocytes. Endogenous adenosine affects complex network function through adenosine receptor-mediated pathways, through mitochondrial bioenergetics, and through adenosine receptor-independent epigenetic functions. Accumulating evidence from our laboratories shows that disruption of adenosine homeostasis plays a major role in epileptogenesis. Conversely, we have found that reconstruction of adenosine’s homeostatic functions provides new hope for the prevention of epileptogenesis. We will discuss how adenosine-based therapeutic approaches may interfere with epileptogenesis on an epigenetic level, and how dietary interventions can be used to restore network homeostasis in the brain. We conclude that reconstruction of homeostatic functions in the brain offers a new conceptual advance for the treatment of neurological conditions that goes far beyond current target-centric treatment approaches.